Field efficacy of different fungicide mixtures in control of net blotch on barley - Stepanović, Miloš; Rekanović, Emil; Milijašević-Marčić, Svetlana; Potočnik, Ivana; Todorović, Biljana; Stepanović, Jelena (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2016)
Seven fungicide mixtures (epoxiconazol + metconazole, boscalid + epoxiconazole,pyraclostrobin + epoxiconazole, prothioconazole + tebuconazole, picoxistrobin +cyproconazole, azoxystrobin + cyproconazole and spiroxamine + tebuconazole + triadimenol) were evaluated for control of net blotch of barley caused by Drechslera teres, as well as yield losses, over the 2010 and 2011 growing seasons. Two applications of the fungicide combination pyraclostrobin + epoxiconazole at the rate of 1.0 l ha-1 were the most effective treatment in controlling the disease and improving yield in both experimental years. Treatments with the fungicide mixtures epoxiconazol + metconazole and spiroxamine + tebuconazole + triadimenol showed the least effectiveness in disease control, as well as yield increase.
Keywords: Fungicides; Chemical control; Net blotch; Barley